Re-Examining Supplier-Induced Demand in Health Care: Comparisons among Patients Affiliated and Not Affiliated with Healthcare Professionals in China - Yafei Si; Zhongliang Zhou; Min Su; Han Hu; Zesen Yang; Xi Chen (Institute of Labor Economics (IZA), 2020)
Doing "more" in healthcare can be a major threat to the delivery of high-quality health care. This study used coarsened exact matching to test the hypothesis of supplier-induced demand (SID) by comparing health care utilization and expenditures between patients affiliated with healthcare professionals and their counterpart patients not affiliated with healthcare professionals. Using the China Labor-force Dynamics Survey (CLDS) in 2014, we identified 806 patients affiliated with healthcare professionals and 22,788 patients not affiliated with healthcare professionals. The matched outpatient proportion of patients not affiliated with healthcare professionals was 0.6% higher (p=.754) than that of their counterparts, and the matched inpatient proportion was 1.1% lower (p =.167). Patients not affiliated with healthcare professionals paid significantly more (680 CNY or 111 USD, p<.001) than their counterparts did per outpatient visit, while patients not affiliated with healthcare professionals paid insignificantly less (2,061 CNY or 336 USD, p=.751) than their counterparts did per inpatient visit. Our results lend support to the SID and highlight the need for policies to address the large outpatient care expenses for patients not affiliated with healthcare professionals. Our study also suggests that as the public becomes more informed, the demand of health care may persist while heath care expenditure per outpatient visit may decline sharply due to the weakened SID. To address misbehaviors and contain costs in health care provision, it is important to realign provider incentives.
Keywords: I11; D82; I12; D90; 330; healthcare professionals; health care utilization; supplier-induced demand; China